Generation of Hepatocyte-Like Cells from in Vitro Transdifferentiated Human Fetal Pancreas - Suchitra Sumitran-Holgersson; Greg Nowak; Shifaan Thowfeequ; Setara Begum; Meghnad Joshi; Marie Jaksch; Anders Kjaeldgaard; Carl Jorns; Bo-Göran Ericzon; David Tosh (Cell Transplantation, 2009)
Although the appearance of hepatic foci in the pancreas has been described in animal experiments and in human pathology, evidence for the conversion of human pancreatic cells to liver cells is still lacking. We therefore investigated the developmental plasticity between human embryonic pancreatic cells and liver cells. Cells were isolated and expanded from 7–8-week-old human fetal pancreata (HFP) and were characterized for the absence and presence of pancreatic and hepatic markers. In vitro expanded HFP were treated with fibroblast growth factor 2 (FGF2) and dexamethasone (DX) to induce a liver phenotye in the cells. These treated cells in various passages were further studied for their capacity to be functional in hepatic parenchyma following retrorsine-induced injury in nude C57 black mice. Amylase- and EPCAM-positive-enriched cells isolated from HFP and treated with FGF2 and DX lost expression of pancreatic markers and gained a liver phenotype. Hepatic differentiation was based on the expression (both at the mRNA and protein level) of liver markers albumin and cytokeratin 19. When transplanted in vivo into nude mice treated with retrorsine, both cell types successfully engrafted and functionally differentiated into hepatic cells expressing human albumin, glycogen, dipeptidyl peptidase, and γ-glutamyltranspeptidase. These data indicate that human fetal pancreatic cells have a capacity to alter their gene expression profile in response to exogenous treatment with FGF2 and DX. It may be possible to generate an unlimited supply of hepatocytes in vitro for cell therapy.